Research on mariculture suitability assessment based on GIS – a case study of sea area in Lianyungang - Gao, Jinzhu; Ding, Jian; An, Taitian; Yang, Xiao (Frontiers in Marine Science, 2025)
IntroductionIn the future, China's mariculture must maintain its scale and improve quality. Crucial measures for achieving this goal are to optimize the layout of sea areas for aquaculture, strengthen the suitability assessment of marine aquaculture, and delineate suitable areas.MethodsThis study aims to scientifically identify marine aquaculture zones suitable for marine spatial planning by constructing a comprehensive suitability assessment system, incorporating both natural and social factors. The weights of the evaluation indicators were determined using the Analytic Hierarchy Process (AHP). Taking the Lianyungang sea area as a case study, GIS technology was employed to analyze marine aquaculture suitability based on the proposed index system.ResultsThe results categorized the Lianyungang sea area into aquaculture zones with varying suitability levels: excellent, good, average, poor, and very poor. Based on these findings, the study further classified the area into three types of management zones: key, moderate, and limited mariculture zones.DiscussionIn order to provide better decision support services and take into account the matching with Marine spatial planning and double evaluation, it is necessary to classify the evaluation results to facilitate users to propose scientific and practical management measures in this paper. Based on the evaluation results of mariculture suitability in the research area, it is necessary to strengthen the protection and development of mariculture suitable areas by providing sufficient resources and maximizing development potential.